2022
DOI: 10.3390/brainsci12111481
|View full text |Cite
|
Sign up to set email alerts
|

Personality Factors as Predictors in Burnout Level Changes for Surgical Area Nurses

Abstract: Surgical area nurses provide comprehensive care to patients throughout the surgical process. Increases in life expectancy lead to the appearance and development of diseases, translating into an increase in the number of necessary interventions. Increases in the workload can be another risk factor for the development of burnout in professionals in this area. Knowledge of psychological and personality-related variables provides relevant information of level changes in the dimensions of burnout syndrome. Three lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In line with predictive models of burnout dimensions, the psychological variables considered were relevant to the students participating in our study, as has been found for experienced nurses. In addition, some variables are specifically relevant to the academic field [56][57][58]. Thus, NE is a predictor of all three dimensions of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…In line with predictive models of burnout dimensions, the psychological variables considered were relevant to the students participating in our study, as has been found for experienced nurses. In addition, some variables are specifically relevant to the academic field [56][57][58]. Thus, NE is a predictor of all three dimensions of burnout.…”
Section: Discussionmentioning
confidence: 99%